Highwall Control At Homestake's Open Cut Mine - Don Berger (International Conference on Ground Control in Mining, 1996)
Highwall scaling, bolting and technical blasting are important aspects in the remediation of existing highwall exposures. Proper planning, design and research are important first steps in the development of long term stability. Research into old workings and their influence on highwall stability control the planning and design. These steps are followed by improvements in blasting techniques, highwall monitoring programs and constant evaluation of the results. Recently, due to a number of factors, the highwalls of the Open Cut Mine have started to deteriorate, creating both operational and potential safety problems. Geologic setting, highwall design, mining operations, old workings and weather have combined to create adverse conditions that have allowed sections of the highwalls to become unstable. Homestake Mining Company has developed a program to alleviate the existing ground control problems and to decrease the effect operations has on future highwall stability.